Efficacy and Safety of Subcutaneous and Oral Semaglutide Administration in Patients With Type 2 Diabetes: A Meta-Analysis - Zhong, Ping; Zeng, Hai; Huang, Miaochun; He, Guoxin; Chen, Zhixia (Frontiers in Pharmacology, 2021)
Background: This meta-analysis aimed to combine the data available from clinical trials to assess the effects of subcutaneous and oral semaglutide administration on glycaemic control, weight management, and safety outcomes in patients with type 2 diabetes (T2D). Methods: We systematically searched for phase 3 randomized controlled trials (RCTs) that compared semaglutide with placebo or other anti-diabetic drugs in T2D patients. The primary outcome was the change from baseline in glycated haemoglobin (HbA1c) levels. Secondary efficacy endpoints included the change from baseline in body weight, achievement of HbA1c targets, and clinically meaningful weight loss. Key safety outcomes were also assessed. Results: In this meta-analysis, 24 trials with a total of 22185 patients were included. Subcutaneous semaglutide administration reduced HbA1c levels (weighted mean difference [WMD]: –1.14% and –1.37%, for 0.5 mg and 1 mg, respectively) and body weight (WMD: –2.73 kg and –4.09 kg, for 0.5 mg and 1 mg, respectively) when compared with placebo; its efficacy was also superior to other anti-diabetic drugs in reducing HbA1c levels (WMD: –0.71% and –0.86%, for 0.5 mg and 1 mg, respectively) and body weight (WMD: –2.65 kg and –3.78 kg, for 0.5 mg and 1 mg, respectively). Oral semaglutide administration was superior to placebo in decreasing HbA1c levels (WMD: –0.96% and –1.02%, for 7 mg and 14 mg, respectively). Moreover, oral administration of 14 mg semaglutide also showed a significant reduction in HbA1c levels (WMD: –0.36%) as compared with other anti-diabetic drugs. Furthermore, oral semaglutide administration resulted in substantial weight loss when compared with other anti-diabetic drugs (WMD: –1.53 kg and –1.73 kg, for 7 mg and 14 mg, respectively). Notably, subcutaneous and oral semaglutide administration also resulted in higher numbers of patients achieving the targets of HbA1c levels and weight loss than placebo and other anti-diabetic drugs. Overall, we noted no clear evidence of detrimental effects on safety endpoints due to semaglutide treatment, except for some gastrointestinal adverse events. Conclusion: Both subcutaneous and oral semaglutide administration could enable the achievement of sufficient glycaemic control and weight management without increasing the risk of hypoglycaemia, which were effective and safe for the treatment of T2D.